Variations of Southern South China Sea characteristics near Pahang - Nur Hidayah Roseli; Mohd Fadzil Mohd Akhir (Universiti Kebangsaan Malaysia, 2014)
Oceanographic cruises in Pahang water in October 2003 and April 2004, monsoon transition months, produce data on water characteristics. The temperature in both months showed higher values in nearshore compared to the offshore stations. The nearshore salinity in both months is lower than offshore stations. Comparatively, there were smaller differences in temperature and salinity in October than in April, with very little variation between nearshore and offshore stations. T-S diagram showed significant differences between October and April water characteristics. According to the water characteristic observations, the temperature and salinity in October was lower than in April, while dissolved oxygen was higher than in April. The lower temperature and salinity taken during the sampling time in October suggested that during this time, the study area already received the influences of strong winds due to upcoming monsoon. The warmer and saltier water obtained in April showed that during this time, the study area was influenced by southwest monsoon.Winds related to rainfall were observed to have impact to the dynamics of water characteristics during both months.